Development of 5-Fluorouracil/pH-Responsive Adjuvant-Embedded Extracellular Vesicles for Targeting αvβ3 Integrin Receptors in Tumors - Jiseung Kim; Eunsol Lee; Eun Seong Lee (MDPI AG, 2024)
To selectively target and treat murine melanoma B16BL6 tumors expressing αvβ3 integrin receptors, we engineered tumor-specific functional extracellular vesicles (EVs) tailored for the targeted delivery of antitumor drugs. This objective was achieved through the incorporation of a pH-responsive adjuvant, cyclic arginine-glycine-aspartic acid peptide (cRGD, serving as a tumor-targeting ligand), and 5-fluorouracil (5-FU, employed as a model antitumor drug). The pH-responsive adjuvant, essential for modulating drug release, was synthesized by chemically conjugating 3-(diethylamino)propylamine (DEAP) to deoxycholic acid (DOCA, a lipophilic substance capable of integrating into EVs' membranes), denoted as DEAP-DOCA. The DOCA, preactivated using N-(2-aminoethyl)maleimide (AEM), was chemically coupled with the thiol group of the cRGD-DOCA through the thiol-maleimide click reaction, resulting in the formation of cRGD-DOCA. Subsequently, DEAP-DOCA, cRGD-DOCA, and 5-FU were efficiently incorporated into EVs using a sonication method. The resulting tumor-targeting EVs, expressing cRGD ligands, demonstrated enhanced in vitro/in vivo cellular uptake specifically for B16BL6 tumors expressing αvβ3 integrin receptors. The ionization characteristics of the DEAP in DEAP-DOCA induced destabilization of the EVs membrane at pH 6.5 through protonation of the DEAP substance, thereby expediting 5-FU release. Consequently, an improvement in the in vivo antitumor efficacy was observed for B16BL6 tumors. Based on these comprehensive in vitro/in vivo findings, we anticipate that this EV system holds substantial promise as an exceptionally effective platform for antitumor therapeutic delivery.